Intravascular lithotripsy to address calcific aortic disease - Christina Supino; Jake Nicholson; Eanas Yassa (Annals of Vascular Surgery - Brief Reports and Innovations, 2024)
Intravascular Lithotripsy (IVL) is a relatively modern endovascular tool accepted for use to address vascular calcification in the iliac arterial system and below. This case study shows evidence of successful application of IVL followed by stent placement to calcific disease present within the aorta as well. A 78-year-old female with numerous comorbidities and a history of an aorto right femoral left iliac bypass graft in 1998 presented with severe lifestyle limiting claudication secondary to high-grade atherosclerotic stenosis of her infrarenal abdominal aorta at the level of the proximal anastomosis of her bypass graft. Initial ABIs were 0.54 and 0.55 on the right and left respectively. Initially the operative plan was to conduct a retroperitoneal aortic endarterectomy. However, after the surgical optimization center deemed the patient intermediate risk and her pulmonary function decreased prior to the procedure, the decision was made to proceed with IVL followed by angioplasty and aortic stent placement. The patient tolerated the procedure well without complication and she was discharged home the following day. At follow up appointment 6 weeks later, the patient's repeat ABIs were significantly improved to 0.77 in the right and 0.86 in the left with a coinciding improvement in symptoms. In conclusion, IVL is safe and effective in calcific aortic disease and should be considered in patients who are not optimal open surgical candidates.